Pengaruh kegiatan praktikum sederhana dalam peningkatan hasil belajar aspek kognitif pada peserta didik kelas III sekolah dasar - Zulaika Qudduus, Gae Sarah; Rintayati, Peduk; Adi, Fadhil Purnama (Jurnal Pendidikan Dasar, 2021)
This study aims to determine the effect of simple practicum activities on improving cognitive aspects of learning outcomes on participant educate class III SD Negeri Gegeran . This study uses a type of experimental quantitative research which uses the Nonequivalent Control Group Design. The location of this research is SD Negeri Gegeran, Arjosari Pacitan District. Data collection techniques using pre-test and post-test . In this study calculate the validity and reliability of the test items. The analysis technique in this study uses normality test, linearity test, and homogeneity test. The hypothesis test used is a simple linear regression test. Based on the analysis of the data, the conclusions obtained are: (1) the normality test in the control class is 0.200 and the experimental class is 0.056, so that both are greater than 0.005 and the data is normally distributed, (2) the linearity test for the control class is 0.646 and the experimental class 0.444 so that it is greater than 0.05 and is linear (3) the effect of simple practicum activities on improving student learning outcomes is evidenced by the hypotheses obtained, namely 0.020 < 0.05 and the effect has a value of 78%.Keywords: Science, Simple Practicum, Learning Outcomes, Cognitive Aspects, Elementary Scholl